The impact of selectins on mortality in stable carotid atherosclerosis - Hoke, Matthias; Winter, Max-Paul; Wagner, Oswald; Exner, Markus; Schillinger, Martin; Arnold, Zsuzsanna; Mlekusch, Wolfgang; Maurer, Gerald; Koppensteiner, Renate; Minar, Erich; Goliasch, Georg (Thrombosis and Haemostasis, 2015)
Cellular adhesion molecules also known as selectins promote recruitment of inflammatory cells into the arterial wall where they interact with lipid particles leading subsequently to plaque formation. The intercellular adhesion molecule-1 (ICAM-1), the vascular cell adhesion molecule-1 (VCAM-1) and the endothelial-leukocyte adhesion molecule 1 (ELAM-1) also known as E-selectin mediate the attachment of leukocytes and have been implicated in the destabilisation of atherosclerotic plaques. Therefore, we hypothesised that plasma selectin levels are associated with adverse clinical outcome. We prospectively studied 855 patients with sonographically confirmed carotid atherosclerosis. During a median follow-up of 6.2 years, corresponding to 5,551 overall person-years, 275 patients (26 %) died. We detected a significant association between cardiovascular mortality and ICAM-1 (adjusted hazard ratio [HR]: 3.43, 95 % confidence interval [CI] 2.00–5.88, p< 0.001) as well as VCAM-1 (adjusted HR: 2.51, 95 % CI 1.45–4.34, p=0.001) when comparing the fourth with the first quartile. Comparable results were obtained for all-cause mortality. In contrast, we could not detect a significant association between E-selectin and all-cause or cardiovascular mortality. We identified the selectins ICAM-1 and VCAM-1 as strong and independent predictors of all-cause and cardiovascular mortality in patients with stable carotid atherosclerosis. These molecules are elevated in states of endothelial activation and might assist to monitor anti-atherosclerotic therapy and select those patients with carotid atherosclerosis, who are at higher risk for cardiovascular events.
Keywords: Cell adhesion molecules; carotid atherosclerosis; risk prediction